On the role of contestations, the power of reflexive authority, and legitimation problems in the global political system - Michael Zürn (International Theory, 2021)
This response to my critics discusses four claims that are central for 'A Theory of Global Governance'. The first claim is that observing a high level of conflict and contestation in world politics is not proof of the unimportance of global governance, since many of the current conflicts and contestations are about international institutions. The second claim is that the 1990s saw a rise of trans- and international authority beyond the nation-state that is essential for the rise of a global political system. Third, a global system of loosely coupled spheres of authority relies on `critical deference' (reflexive authority) but also contains numerous elements of coercion. And fourth, a technocratic legitimation of intrusive international authorities cannot build on emotions or a sense of belonging. This deficit creates a political opportunity structure that allows for the rise of a myriad of dissenters. The relative importance of them depends on the availability of resources for mobilization and not on the quality of reasons for resistance.
Keywords: 300; global governance; nationalism; coercion; dissent; theory